Conjugate System of Professional Teacher Education - D. S. Tkach (Vestnik MGIMO-Universiteta)
The article deals with the main ways of modernization of the educational system. The author dwells on the notion of “the interconnected education system” and describes its structure, types of interconnections and social effects of this model on those involved in the educational environment of Russia.